The Maintenance of Tobaru Language in Tabanga Comunity at Sulamadaha Village Ternate City: A Sociolinguistic Study - Sri Yulan Sari; Ismail Maulud; Ikmal Muhammad; Farida Maricar; Nurprihatina Hasan; Nurain Jalaludin (CV. Eureka Murakabi Abadi, 2022)
This study discusses the maintenance of the Tobaru language. The purpose of this study is to describe the maintenance of the Tobaru language in the Tabanga community and describe the factors that support the maintenance of the Tobaru language in the Tabanga community. The method used is qualitative-descriptive in a randomized technique. Data obtained through observation, interviews, and questionnaires. The data of this study were analyzed using the Fishman realm theory. The results of this study is Tobaru language by the speaking community, especially in the family domain by 70% for parents and 30% for children, in the neighboring domain at 70% for parents and 30% for children, and jobs by 70%. And the supporting factors for maintaining the Tobaru language are seen from the pride and loyalty factor of the Tobaru people by 80%, the regional concentration and migration factors can be seen from the isolated condition of the Tabanga area, family environmental factors that show family members who still use the Tobaru language by 80%, community environmental factors indicate that 80% of the community is still actively using the Tobaru language, and religious factors who show that the majority of the Tabanga community are Protestant Christians and Pentecostal Christians. It can be concluded that Tobaru language still can survive in the realm of religion.